The effect of -carotene supplementation above requirement on the production and reproduction performance of female sheep and goats - A mini review - Ahmed, Osman; Hassen, Abubeker; Lehloenya, Khoboso (Syiah Kuala University, 2024)
The high rate of metabolic activity during breeding, pregnancy, parturition and lactation may lead to oxidative stress in sheep and goats. Antioxidant supplementation is proposed as a therapy for encountering resultant stress. In animals, -carotene functions mainly as pro-vitamin A and as a scavenger of free radicals, especially against singlet-state oxygen. This raises the question of whether supplementing -carotene as an antioxidant above the vitamin A requirement is beneficial. While a number of studies have been conducted on the effect of -carotene supplementation as a tool to improve the production and reproduction performance of female goats and sheep, the findings are inconsistent. Some of the main reasons for this inconsistency could be attributed to the variation in the amount of -carotene supplemented, the amount of -carotene in the animal diet and the difference in the animal requirement for -carotene. The objective of this review was to determine the effects of -carotene supplementation on the production and reproductive performance of female sheep and goats fed on a diet deficient or not deficient in -carotene. Data were extracted from peer-reviewed articles that were searched in the Web of Science, Google Scholar and Scopus databases. Thirteen peer-reviewed published articles were found on the subject under review. We estimated the animal requirement for -carotene, the amount of -carotene provided to the animal in the diet and the amount of -carotene supplementation used in each study. These estimations were made to indicate whether the diet fulfilled the animal's requirement for -carotene or not. The review revealed that -carotene supplementation enhances the production and reproduction performance of the sheep when fed on a carotene-deficient diet. Additionally, -carotene supplementation may increase the levels of some hormones such as progesterone in sheep and goats when fed on a diet that fulfils their requirements of -carotene. However, the supplementation of -carotene above the requirements seems to not affect the production and reproduction parameters such as body weight, milk production, estrus parameters, conception rate, pregnancy rate, and litter size.In conclusion, while -carotene supplementation is essential for female sheep and goats fed -carotene-deficient diets to attain optimal production and reproductive performance, supplementing -caroteneabovethe requirements does not appear to provide any further benefits to their overall performance.